Legal regime of property registration: civil-legal aspect - Serdyuk R. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького, 2024)
Purpose. The purpose of the work is to analyze the legal regime of property registration, to identify shortcomings, gaps and contradictory legislation, to develop a scientific approach to solving controversial issues. Methodology. The methodology includes the application of general scientific and special legal methods of scientific knowledge, in particular: dialectical, systemic analysis, induction and deduction, comparative legal, prognostic legal. Results. The article identifies the lack of a single approach to determining the branch affiliation of the legal regime of real estate registration due to the dominance of the approach of understanding this category as a “procedural legal relationship” regulated by mandatory acts of administrative legislation. Moreover, the state registration itself among civilians is considered as a legal fact with which the law connects the emergence, change, or termination of legal relations, which is caused by the emergence, change, or termination of property rights to immovable or equivalent movable property. It is substantiated that the scientific approach, according to which in inheritance relations the fact of state registration of rights to inherited property has a legal character and retrospectively determines the emergence of rights to such property by the person who entered the inheritance, is debatable. Originality. The position is expressed regarding the evidentiary value of the state registration of rights arising from the moment of acceptance of the inheritance, rather than the legal value (legal fact). The need for legal certainty of the legal regime of inherited property from the moment of the testator’s death to the moment of its acceptance by the heir is substantiated. A regime of “legal protection” of property and property rights to it is proposed for such cases. The need for a regulatory definition at the level of the Civil Code of Ukraine was determined: the legal meaning of the declaration of will as a unilateral deed of the testator, as an act of declaration of will to acquire ownership rights to the housing object of the state housing fund, which gives the heirs the right to claim the inherited property. It has been established that in the legal positions of the Supreme Court there was a departure from the criteria laid down in clause 13 of the Resolution of the Plenum of the Supreme Court “On judicial practice in cases involving claims for the protection of the right to private property” dated 05.25.1998, according to which such a right of claim to heirs was recognized only if the testator’s application for privatization was not considered within the period established by law or its satisfaction was illegally refused. Currently, such a single criterion according to the Legal position determined in case No. 6-121cs13 dated 11.12.2013 is the declaration of the will of the testator (tenant of the object of the state housing fund) in the form of an application for the privatization of such housing, submitted to the privatization body. The need for regulatory certainty of the legal regime of real estate and registration of rights to it of subjects of the Russian Federation or related to it during the period of martial law at the level of the law is argued. It was determined that they are determined by the legal status of the entity that owns the property rights to it. Practical significance. The results of the research can be used in law-making activities to improve the current legislation in the field of registration of rights to real estate and in law enforcement when resolving disputes and implementing rights protection in the field of registration of rights to real estate.